THE IMPORTANCE OF REGISTRATION OF THE SHIPOWNER APPAREL TRADEMARK AT THE DIRECTORATE GENERAL OF INTELLECTUAL PROPERTY - Raihan Radinka Yusuf; Hari Sutra Disemadi (Universitas Internasional Batam, 2022)
There are so many new brands or products that are popping up at this time. However, with so many new brands and products, it is possible that there will be a dispute, one of which is plagiarism against a particular brand. Therefore, it is very important to maintain the rights to the mark by registering the mark with the Directorate General of Intellectual Property. Registration of a mark aims to ensure that the mark gets legal protection from the state. Shipowner Apparel is one of the businesses engaged in the fashion sector. However, the trademark has not been registered because the business owner is still unfamiliar with the trademark rights. So in this case the aim is to register to avoid disputes related to trademarks that may occur in the future. Community Service (PkM) is carried out with 3 stages of implementation methods, namely pre-implementation, implementation stage and evaluation stage. The result of the implementation of this community service is in the form of education regarding the importance of intellectual property protection. as well as a receipt for an online application for registration of the Shipowner Apparel trademark